Design of surface plasmon resonance based both side polished photonic crystal fiber for highly efficient refractive index sensor - Ramani U.; Kumar H.; Singh B.K.; Pandey P.C. (My University, 2025)
In this paper, both sides flat photonic crystal fiber-based surface plasmon resonance (PCF-SPR) sensor has been proposed. In this external sensing mechanism based sensor, we have used gold as plasmonic material with an adhesive TiO2 layer over it, enhancing the interaction between analyte channel and gold metal. Using the wavelength interrogation and amplitude interrogation method, the maximum wavelength and amplitude sensitivities are obtained 22,800 nm/RIU and 947 RIU−1, respectively, for analyte range 1.30–1.40 with a maximum wavelength resolution of 4.38 × 10−6. With Full-width half maxima (FWHM) around 45 nm, the sensor provides a high figure of merit (FOM) 507 RIU−1. The proposed sensor can be fabricated from newly available technologies such as the sol-gel method, stack and draw method for several practical applications in the bio-medical field, bio-chemical field to provide higher and accurate sensing results. The presented sensor has also played a vital role in cancer cell detection with higher sensing performance. © 2021 Elsevier GmbH